2019
DOI: 10.21815/jde.019.060
|View full text |Cite
|
Sign up to set email alerts
|

Educator and Student Hand Hygiene Adherence in Dental Schools: A Systematic Review and Meta‐Analysis

Abstract: Health professionals and their patients are subject to cross‐contamination and potential exposure to harmful infectious diseases. A common form of cross‐contamination is through dental procedures without proper instrument care and lack of hand hygiene. The aim of this systematic review was to evaluate the published research on the adherence of educators and students in academic dental institutions to hand hygiene procedures. This systematic review was conducted according to the Preferred Reporting Items for Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
(79 reference statements)
1
6
0
2
Order By: Relevance
“…20 Knowledge level and practice of infection control measures, such as hand hygiene, were found to be poor among dental students. 21,22 Similar to the AIDS pandemic in the 1980s, the COVID-19 crisis serves to heighten the awareness of dental aerosolization, pushing dentists to revisit clinical safety standards 23 and encouraging dental schools to regard infection control-teaching as a significant part of dental education. 20 In addition to developing online and offline combined teaching method, focusing on the psychological status of residents, and establishing evaluation system of COVID-19 infection control, WHUSS has implemented measures to narrow the gap of the reduction of clinical operating opportunities of residents due to area divisions for infection control and financial pressure from PPE supplies of departments.…”
Section: Discussionmentioning
confidence: 99%
“…20 Knowledge level and practice of infection control measures, such as hand hygiene, were found to be poor among dental students. 21,22 Similar to the AIDS pandemic in the 1980s, the COVID-19 crisis serves to heighten the awareness of dental aerosolization, pushing dentists to revisit clinical safety standards 23 and encouraging dental schools to regard infection control-teaching as a significant part of dental education. 20 In addition to developing online and offline combined teaching method, focusing on the psychological status of residents, and establishing evaluation system of COVID-19 infection control, WHUSS has implemented measures to narrow the gap of the reduction of clinical operating opportunities of residents due to area divisions for infection control and financial pressure from PPE supplies of departments.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to inadequate practice of infection control. A systematic review that included studies from Brazil, United Kingdom, and France, studying the adherence of educators and students in academic dental institutions to hand hygiene procedures, found that hand hygiene among dental students did not even reach 50% of the total number of students 11 …”
mentioning
confidence: 99%
“…14 However, the literature has demonstrated that compliance with hand hygiene is not as high as desired and ranges from 35% to 56%. [45][46][47] In this study, compliance with hand hygiene improved from 92.5% in 2019 to 96.2% in 2020. With respect to adherence to infection control standards according to gender, it was interesting to find that more male than female dental students were compliant.…”
Section: Discussionmentioning
confidence: 55%